The Effect of the Investors’ Sentiment on the Trade-Off between Earnings Management Strategies: The Case of Tunisian Market - Aida Boudabbous; Saoussen Boujelben; Mouna Abdelhedi (Asian Academy of Management Journal of Accounting and Finance, 2021)
The aim of this study was to provide evidence to the benefit of an emerging market on whether and how the prevailing investors’ sentiment influences the earnings management tactics i.e. accrual earnings management and real earnings management. used data related to Tunisian listed firms over the period 2009–2018. We measure the investors’ sentiment index using Google search volume approach. We estimated a recursive equation system to investigate the effect of the investors’ sentiment on the trade-off decision between accrual earnings management and real earnings management. First, in line with the catering theory we found that optimistic period is an opportune occasion that encourages Tunisian managers to upward their earnings whether by accrual earnings management or by real earnings management. Indeed, Tunisian managers are likely to rely on abnormal cash- flows. Second, we found that the Tunisian managers, use both techniques as complementary rather than substitutes. However, during high sentiment period, this complementary relation decreases which may be explained by total cost of earnings management tools. Our results give the investors and the financial analysts, within emerging markets, important insights and requires them to adopt necessary adjustments to their expectations when evaluated from an optimistic market’ perspective. During such periods, they should be more cautious to the possible distortions of reported earnings made by managers. Our research differs from previous studies dealing with the implication of behavioral biases on accounting policies from two viewpoints. First, it advances knowledge to the benefit of emerging contexts, which is still embryonic. Such contexts have their uniqueness regarding the economic, social and political environment making evidence drawn from developed contexts questionable. Second, we address this query in a more comprehensive way. We were interested in examining the effect of the investors’ sentiment on each of earnings management technique taken individually as well as on the possible trade-off between them.